Development of Mathematic Learning Devices Through The Application of The Problem Based Learning Model to Facilitate KPMM in Number Pattern Materials - Payasto, Eko; Maimunah, Maimunah; Saragih, Sehatta (FKIP-Universitas Riau, 2021)
This research is motivated by the low ability of students to solve mathematical problems (KPMM) and the teacher has not been optimal in developing mathematics learning tools independently. The purpose of this study was to produce mathematics learning tools through the application of the Problem Based Learning (PBL) model to facilitate KPMM students of SMP Negeri 2 Pangkalan Lesung on number pattern material. This type of research is development research using the 4-D model. Learning tools developed in the form of syllabus, lesson plan (RPP) and student worksheets (LKPD) and KPMM questions. The instruments in this study were validation sheets and student questionnaires. Validation sheets consist of syllabus validation sheets, lesson plans validation sheets, and student worksheet validation sheets, while student questionnaires are in the form of student response sheets. Based on the results of the validation analysis, it shows that the device being developed is very valid. The result of the validation of the syllabus was 3.79; the average RPP score was 3.67; and the average LKPD score was 3.66. The student response questionnaire on the small-scale test showed an average percentage of 94.67% with the very practical category. The learning tools developed were valid and practical for use by students of SMPN 2 Pangkalan Lesung.